2021
DOI: 10.1186/s40659-021-00349-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between single-nucleotide polymorphisms in miRNA and breast cancer risk: an updated review

Abstract: Breast cancer (BC), a heterogeneous, aggressive illness with high mortality, is essentially a genomic disease. While the high-penetrance genes BRCA1 and BRCA2 play important roles in tumorigenesis, moderate- and low-penetrance genes are also involved. Single-nucleotide polymorphisms (SNPs) in microRNA (miRNA) genes have recently been identified as BC risk factors. miRNA genes are currently classified as low-penetrance. SNPs are the most common variations in the human genome. While the role of miRNA SNPs in BC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 111 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…More extensively, the ssc-miR-21-5p had six isoforms that were detected that differed in three nt at the 3’-terminus and again showed a broad range of differential expression in the PAMs. These results imply some understudied molecular complexity of porcine miRNA regarding individual polymorphism and potential functional divergence ( 36 , 37 ).…”
Section: Resultsmentioning
confidence: 90%
“…More extensively, the ssc-miR-21-5p had six isoforms that were detected that differed in three nt at the 3’-terminus and again showed a broad range of differential expression in the PAMs. These results imply some understudied molecular complexity of porcine miRNA regarding individual polymorphism and potential functional divergence ( 36 , 37 ).…”
Section: Resultsmentioning
confidence: 90%
“…In particular, 2–3 subforms of luminal BCs were established [ 47 ] and basal cell types of cancers were reclassified into triple negative (TN) BCs with “basal-like” and “non-basal like” features using EGFR and CK5/6 markers, respectively, and their subtyping continues ( Figure 2 ) [ 19 , 48 ]. Each BC seems to be morphologically and genetically unique, thus determining that the clinical manifestations of the disease are needed for personalized therapy for each patient [ 49 ].…”
Section: Molecular Subtypes Of Bcmentioning
confidence: 99%
“…Single-nucleotide mutations in miRNAs may impact miRNAs expression, thereby affecting the susceptibility to diseases and prognosis ( 18 , 19 ). Of note, a study conducted in a northern Chinese population demonstrated that polymorphism at the rs121224 locus of miR-365 gene was associated with both the susceptibility to and prognosis of intestinal gastric cancer ( 20 ).…”
Section: Introductionmentioning
confidence: 99%